Long Survival of a Patient with Trisomy 18 and Dandy-Walker Syndrome - Leonardo Moura Ferreira de Souza; Augusto Galvão e Brito Medeiros; José Paulo Ribeiro Júnior; Aurea Nogueira de Melo; Sylvyo André Morais Medeiros Dias (Medicina, 2019)
Trisomy 18 is a genetic disease resulting from an extra chromosome 18, characterized by a broad clinical spectrum, poor prognosis and low rates of survival. This is the case of a 12 year-old girl diagnosed with full trisomy 18, and multiple malformations, including Dandy-Walker Syndrome and congenital heart defects on long term survival. At nine months, a new echocardiogram showed a double outlet right ventricle, significant pulmonary stenosis, patent ductus arteriosus and ventricular septal defect. Cardiac surgery was performed at one year and seven months. Early surgical intervention and multidisciplinary follow-up may change the clinical outcome of the disease. Further studies are required to evaluate the benefit of invasive procedures such as cardiac surgery on survival of patients with trisomy 18.